ANALISIS PENYELESAIAN SENGKETA KEPEMILIKAN TANAH ANTARA KOPERASI TANI TIMIANGAN RAYA (KTTR) DENGAN DEWI ROBINAR - Almadison, (SUNGKAI, 2023)
So important is land for human life, regulations are needed that regulate the use, allocation, control and ownership of land, along with the resolution of land disputes. Saturday, September 24 1960, was a very important day in the development of Indonesian law, especially in the field of Agrarian law. This historic date is the day Law No. 5 years known as the Basic Agrarian Principles Regulations. As forobjectiveUUPA is asBasic Law laying the foundations for legal draftingagrarianational, which will constitute a tool to bring prosperity, happiness and justice for the country and the people, especially farmers, in the framework of a just and prosperous society.NHowever, in reality there is an increase in the number of land disputes every year. Land disputes are unavoidable nowadays. The law enforcement bureaucracy in resolving land disputes through litigation and non-litigation is often found to be considered unfair in resolving these disputes. From these various cases, the emergence and sharpening of land disputes did not occur instantly, but rather grew and developed from seeds that had been buried for a long time. Such as the land ownership dispute between the Timiangan Raya Farmers Cooperative (KTTR) and Dewi Robinar. The Timiangan Raya Farmers Cooperative sued on October 5 2021 with no. Reg; 254/Pdt.G/2021/PN Prp. on suspicion of grabbing land on a 250 ha plantation owned by Dr.dr.Dewi Robinar, Sp.A. (K) since 2005 in Lubuk Napal Village, Rambah Samo District, Rokan Hulu Regency, meaning that this problem has been hidden for 18 years and was only revealed in 2021. In accordance with article 33 number 4 of the 1945 Constitution which states that the national economy is organized based on economic democracy with the principles of togetherness, efficiency, justice, sustainability, environmental insight, independence and maintaining the balance of progress and national economic unity. The various provisions and efforts mandated in it are expressly aimed at raising the standard of living of the economically weak people.In this research the method is used as an analytical tool is an approach taken based on the main legal basis by examining theories, concepts, legal principles and laws and regulations related to pThis research is with analytical descriptive research specifications. With data analysis used is qualitative data analysis.